UHMWPE wear particles and dendritic cells promote osteoclastogenesis of RAW264.7 cells through RANK-activated NF-κB/MAPK/AKT pathways - Zhang, Jianzhi (Int J Clin Exp Pathol, 2017)
Dendritic cells (DCs) were shown to enhance UHMWPE particle promoted osteoclastogenesis in RAW264.7 macrophages. This study aimed to elucidate the signaling network mediating the osteoclastogenic effects of UHMWPE particles and DCs. RAW264.7 cells were induced with UHMWPE particles and /or DC2.4 cells. The expression of Rank was silenced by shRNA. The activation of p38MAPK, AKT, and NF-κB was inhibited specific inhibitors. The osteoclasts were assessed by TRAP staining. The expression of osteoclastogenic genes and activation of p38MAPK, AKT, and NF-κB were analyzed by qPCR and/or Western blot. UHMWPE particles and DC2.4 cells cooperatively induced RAW264.7 macrophages to differentiate into osteoclasts, activated p38MAPK, AKT, and NF-κB pathways, and upregulated Nfatc1 and osteoclast markers, which was abolished by silencing Rank or inhibited by inhibitors of p38MAPK, AKT, and NF-κB in RAW264.7 cells. These data demonstrated the complexity of signaling network and cell-cell interactions involved in UHMWPE particles-induced osteolysis.